PERANCANGAN USER INTERFACE APLIKASI MOBILE START-UP KOS.KU MENGGUNAKAN METODE USER CENTERED DESIGN - Mahasinul Akhlak, Muhammad Lutfi; Azizah, Isnaini Nurul; Nastiti, Putri -; Wulan, Retno - (STMIK BINA PATRIA, 2024)
So far, students have looked for information about boarding houses in conventional ways, including by visiting boarding houses directly to carry out surveys about the conditions, prices and facilities of boarding houses. The digital start-up Kos.ku is designed to find solutions and bridge these difficulties by connecting boarding house seekers and boarding house partners who are able to provide the housing that students (boarding house seekers) want. In this research, the method used is user centered design, analysis using SWOT and feasibility study analysis using TELOS. The testing process was carried out through prototype tools in the Figma software, everything ran according to user flow with test results of 87% (see table 3). This proves that the digital start-up designed has answered user needs.